Impact of Shading on the I-V Characteristics and Power Output of Monocrystalline and Polycrystalline Solar Panels - Lesmana, Andyka; Yan Dewantara, Belly; Diah Prahmna K., Iradiratu (Emitor: Jurnal Teknik Elektro, 2024)
Solar panel is a tool composed of several solar cells assembled in series or parallel by utilizing the photovoltaic effect so that it can convert solar energy into electrical energy. Solar panels have several types, namely monocrystalline and polycrystalline where each type of solar panel has different absorption efficiency based on the constituent materials. According to several surveys, obstacles that often occur in the field in the installation of solar panels are due to external influences which include influences (shading, soiling, and spot) so that it has an impact on the performance of solar panels which results in power instability due to non-linear current-voltage (I-V) relationships. This study tested the power output of monocrystalline and pollycrystalline 100 Wp solar panels with several levels of shading testing The results of testing research data that have been carried out show that there is an influence of shading on current and voltage, resulting in a decrease in output power. It was found that the partial and overall shading effects caused a decrease in power by -71% and -75% respectively from the normal conditions of monocrystalline solar panels. Polycrystalline solar panel testing due to partial shading effect of -75% and total shading of -77% of normal solar panel output power without conditioning.